Environmental conditions and time of collection influence the production of essential oil from the leaves of Lippia sidoides on the coast of Ceará (Research, Society and Development, 2022)
The literature points out that in addition to influences such as temperature, humidity and cultivation techniques, other variables interfere in the production of essential oils by aromatic plants, highlighting the seasonality and circadian cycle of the plant. This study aims to evaluate the influence of some environmental conditions on the production of essential oils from Rosemary-pimenta (Lippia sidoides Cham.). Collections carried out in October-November/2019 in the medicinal plant garden of Faculdade do Vale do Jaguaribe, Aracati-Ceará. The collection was completely randomized and divided into four times (6:00 am, 10:00 am, 2:00 pm and 6:00 pm), and with four repetitions and one with duplicates. Statistical analysis was performed using Student's t test, considering p < 0.05. The samples showed lower humidity (60.5%) at 10 am, on the other hand, at 6 am a higher humidity was verified (64.1%). The analyzes showed that the largest amounts of essential oil, in relative terms, are produced at 10 am (20.8%). Room temperature has a positive relationship with dry leaf weight and a negative relationship with leaf moisture. Thus, the essential oil contents are influenced by different variables, recommending the harvest in this garden at 10 am.